2013
DOI: 10.1182/blood-2012-08-449272
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocyte-specific deletion of the protein-tyrosine phosphatases Shp1 and Shp2 causes abnormal megakaryocyte development, platelet production, and function

Abstract: Key Points• The protein-tyrosine phosphatases Shp1 and Shp2 are critical regulators of megakaryocyte development, platelet production, and function.• Shp1 and Shp2 perform mainly distinct functions in megakaryocytes and platelets, with little functional overlap.The SH2 domain-containing protein-tyrosine phosphatases Shp1 and Shp2 have been implicated in regulating signaling from a variety of platelet and megakaryocyte receptors.In this study, we investigate the functions of Shp1 and Shp2 in megakaryocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 48 publications
6
88
1
4
Order By: Relevance
“…Mutations in PTPN11 occur in 50% of patients, SOS1 in 13%, RAF in 3-17%, and KRAS in less than 5% [7]. PTPN11 encodes SH2 domain, which contains protein-tyrosine phosphatases Shp1 and Shp2; Shp1 is expressed in hematopoietic and epithelial cells, while Shp2 is expressed widely and they are both key regulators in megakaryocyte development, platelet formation, and function (including interaction with collagen and fibrinogen); these two phosphatases seem to have opposite roles in platelet function (Shp1 reduces platelet response to collagen and fibrinogen by positively regulating immune receptor tyrosine-based activation motif-containing receptors and integrin signaling, whilst Shp2 behaves in the opposite way) [8].…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in PTPN11 occur in 50% of patients, SOS1 in 13%, RAF in 3-17%, and KRAS in less than 5% [7]. PTPN11 encodes SH2 domain, which contains protein-tyrosine phosphatases Shp1 and Shp2; Shp1 is expressed in hematopoietic and epithelial cells, while Shp2 is expressed widely and they are both key regulators in megakaryocyte development, platelet formation, and function (including interaction with collagen and fibrinogen); these two phosphatases seem to have opposite roles in platelet function (Shp1 reduces platelet response to collagen and fibrinogen by positively regulating immune receptor tyrosine-based activation motif-containing receptors and integrin signaling, whilst Shp2 behaves in the opposite way) [8].…”
Section: Resultsmentioning
confidence: 99%
“…Alexandra et al recently showed that deletion of Shp1 in mice resulted in platelets being less responsive to CRP by reducing both GPVI expression and signaling via the Src-Syk-PLCg2 pathway. 37 On the contrary, deletion of Shp2 resulted in platelets being hyper-responsive to agonists. 37 Although the phosphorylation of Shp1 Y564 and Shp2 Y580 was suppressed in PIRB-TM platelets in response to CRP, the distinct roles of Shp1 and Shp2 in platelet activation suggest that PIRB negatively regulates platelet activation, probably by enhancing the phosphatase activities of Shp2 instead of Shp1.…”
Section: Discussionmentioning
confidence: 99%
“…37 On the contrary, deletion of Shp2 resulted in platelets being hyper-responsive to agonists. 37 Although the phosphorylation of Shp1 Y564 and Shp2 Y580 was suppressed in PIRB-TM platelets in response to CRP, the distinct roles of Shp1 and Shp2 in platelet activation suggest that PIRB negatively regulates platelet activation, probably by enhancing the phosphatase activities of Shp2 instead of Shp1. However, further investigation will be needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of spinophilin also results in reduced cAMP synthesis in response to PGI 2 , highlighting multiple functions of this scaffold protein in platelets. Studies on SHP‐1‐deficient mice have identified a main role of SHP‐1 in regulating GPVI and integrin αIIbß3 signaling but did not reveal any defect in GPCR signaling 39. Because SHP‐1 is ablated during megakaryocyte differentiation in these mice, it is possible that the role of SHP‐1 in regulating GPCR signaling is not apparent because of compensatory mechanisms and/or redundancy with the closely related SHP‐2 phosphatase.…”
Section: Interactions At Receptor Levelmentioning
confidence: 97%
“…Because SHP‐1 is ablated during megakaryocyte differentiation in these mice, it is possible that the role of SHP‐1 in regulating GPCR signaling is not apparent because of compensatory mechanisms and/or redundancy with the closely related SHP‐2 phosphatase. Indeed, platelets deficient in both SHP‐1 and SHP‐2, display marked defects in PAR4 receptor signaling, suggesting a level of redundancy 39. Whether a spinophilin/RGS18 complex exists in SHP‐1 deficient platelets remains to be determined.…”
Section: Interactions At Receptor Levelmentioning
confidence: 99%